KONSISTENSI PERDA NOMOR 14 TAHUN 2011 TENTANG RENCANA TATA RUANG KOTA SEMARANG 2011-2031 DALAM PERSPEKTIF PEMBANGUNAN YANG BERkELANJUTAN - Muhammad Junaidi (Jurnal Ius Constituendum, 2016)
Environmental problems can NOT be released from the arrangement of spaceproblems in Indonesia, as well as THE issue occurred in the city of Semarang. It is caused by Singer Development Activities The city ASPECTS NOT pay attention to the Environment. In HAL embodies Sustainable Development, City of Semarang LocalRegulation No. 14 Year 2011 CONCERNING Spatial Plan Semarang from 2011 to 2031, as the legal umbrella of the City Government of Semarang hearts set Spatial city. Operates SPECIAL Research singer explained how consistency Regional Regulation No.14 of 2011 Against the Law on Spatial Planning No. 26 of 2007 and Law on the Protection and Management of the Environment No. 32 of 2009, as the Guidelines, Tutorial, and Strategy For the City of Semarang hearts held Governance And Development Activities spatial. The method which was used hearts Research singer, using methods of normativejuridical approach, Research singer seeks to review conduct an inventory of positive law and principles of the law incronceto to review then performed sinkronsiasi hearts HAL singer Regulation No. 14 Year 2011 CONCERNING Spatial Plan Semarang 2011 -2031 WITH Devices legal rules structuring space, as well as the Protection and Management of the Environment The previous beraku Currently in Indonesia.